Humbug and outrage: A study of performance, gender and affective atmosphere in the mediation of a critical parliamentary moment. (February 2023) - Parry, Katy; Johnson, Beth
In a Parliament called back following its unlawful prorogation in September 2019, Prime Minister Boris Johnson touched a raw nerve by stating that the 'best way to honour Jo Cox's memory is to get Brexit done'. Johnson had earlier dismissed concerns about threats to Members of Parliament which echoed his inflammatory language as 'humbug'. We examine this critical parliamentary moment in the context of broader discussions about emotionality, toxic discourse and polarisation in the United Kingdom. The study combines performance analysis of the Hansard transcripts and UK Parliament YouTube coverage of the debate, with discourse analysis of national and local newspaper coverage from 25 September to 1 October 2019. We contend that in-depth examination of this moment, alongside the subsequent journalistic commentary, contributes an original case study which works to illuminate the intersections of political performance, affective atmospheres and gender in contemporary mediated political culture.